Volatile Liquid Detection by Terahertz Technologies - Baxter, Harry W; Worrall, Adam A; Pang, Jie; Chen, Riqing; Yang, Bin (Frontiers in Physics, 2021)
The prospect of being able to move through security without the inconvenience of separating liquids from bags is an exciting one for passengers, and there are important operational benefits for airports as well. Here, two terahertz (THz) systems, 100 GHz sub-THz line scanner and attenuation total reflection-based THz time domain spectroscopy (TDS), have been used to demonstrate the capability of identifying different liquid samples. Liquid samples’ THz complex permittivities are measured and their differences have contributed to the variation of 100 GHz 2D images of volatile liquids with different volumes inside of cannister bottles. The acquired attenuation images at 100 GHz can easily be used to distinguish highly absorbed liquids (Water, Ethanol, Fuel Treatment Chemicals) and low loss liquids (Petrol, Diesel, Kerosene and Universal Bottle Cleaner). The results give a promising feasibility for mm-wave imager and THz spectroscopy to efficiently identify different volatile liquids.